2023
DOI: 10.1007/s00497-023-00463-w
|View full text |Cite
|
Sign up to set email alerts
|

MLPK function is not required for self-incompatibility in the S29 haplotype of Brassica rapa L.

Abstract: Key message S29 haplotype does not require the MLPK function for self-incompatibility in Brassica rapa. Abstract Self-incompatibility (SI) in Brassicaceae is regulated by the self-recognition mechanism, which is based on the S-haplotype-specific direct interaction of the pollen-derived ligand, SP11/SCR, and the stigma-side receptor, SRK. M locus protein kinase (MLPK) is known to be one of the positive effectors of the SI response. MLPK directly interacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In a separate study, analysis of a self-fertile B. rapa cultivar identified the membrane-localized protein kinase MLPK as a potential effector of SRK ( Kakita et al 2007 ). However, MLPK function is not required for the operation of at least one S haplotype in B. rapa ( Ohata et al 2023 ). Moreover, neither the SRK-ARC1-Exo70A1 pathway nor MLPK are required for the SI response in transgenic self-incompatible A. thaliana plants ( Kitashiba et al 2011 ; Nasrallah and Nasrallah 2014 ).…”
Section: Stop Signals At the Pollen–stigma Interface For Incompatible...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, analysis of a self-fertile B. rapa cultivar identified the membrane-localized protein kinase MLPK as a potential effector of SRK ( Kakita et al 2007 ). However, MLPK function is not required for the operation of at least one S haplotype in B. rapa ( Ohata et al 2023 ). Moreover, neither the SRK-ARC1-Exo70A1 pathway nor MLPK are required for the SI response in transgenic self-incompatible A. thaliana plants ( Kitashiba et al 2011 ; Nasrallah and Nasrallah 2014 ).…”
Section: Stop Signals At the Pollen–stigma Interface For Incompatible...mentioning
confidence: 99%
“…relates to the induction of autophagy in self-pollinated papillae ( Abhinandan et al 2022 ): autophagosomes, which are proposed to function as an additional process for clearing compatibility factors, have been observed in the papillae of self-incompatible Arabidopsis plants but not in those of Brassica ( Table 2 ). Setting aside the curious intraspecific difference regarding the requirement of MLPK in SI ( Ohata et al 2023 ), two possible explanations for the discrepancies observed between Brassica and Arabidopsis may be advanced. One explanation is that the role of MLPK, ARC1, Exo70A1, and autophagy in SI is not universal among crucifers and that distinct SRK-mediated pollen rejection pathways may operate in different species.…”
Section: Stop Signals At the Pollen–stigma Interface For Incompatible...mentioning
confidence: 99%
“…Two distinct forms of MLPK , MLPK form 1 ( MLPKf1 ) and MLPK form 2 ( MLPKf2 ), localize to the papilla cell membrane and directly interact with SRK to transduce SI signaling ( Kakita et al., 2007 ). The Chiifu accession carries the S 60 haplotype on chromosome A07 ( Yamamoto et al., 2023 ), characterized by MLPK -dependent self-incompatibility ( Ohata et al., 2023 ). However, the practical challenge of breeding self-compatible Chinese cabbage lines based on MLPK remains unresolved.…”
Section: Introductionmentioning
confidence: 99%